Peranan Kondisi Tanah terhadap Jumlah Telur Belalang Kembara (Locusta migratoria L.) di Kecamatan Pakuan Ratu, Way Kanan, Lampung = The Contribution of Soil Condition to The Number - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
The objective of this research, which was held in October. 2000, was to know the contribution of soil conditions to the number of migratory locust's eggs in Pakuan Ratu District, Way Kanan Regency, Lampung Province. The methods used in the research were field survey and analysis of soil samples in the labs. The survey was done by exploring predetermined the grade lines. The number of observation spots were 12, and each were replicated three times. The observations were consist of dependent variable (the number of the eggs) and independent variable (field's condition and the soil physical characteristics both in the field and in the labs). Statistical analysis was done using stepwise regression method in order to determine independent variable, which contributes to the number of eggs. Degree of structure, maximum soil temperature, and soil texture tended to have significant contribution to the number of migratory locust's eggs. The elevation of the place, the slope, the soil's type and class of structure, consistency, minimum soil temperature, soil humidity, particle density, bulk density, permeability, Atterberg value, pore size distribution, pH, content of organic matter, organic of C, total of N and C/N Ratio tended to have insignificant contribution to the number of eggs. The suitable soil condition for migratory locust eggs were weak degree of structure, maximum soil temperature 32,31 Â°C and soil texture